Pengaruh Roleplay Pendidikan Kesehatan Tentang Pertolongan Pertama Pada Kecelakaan (P3K) Terhadap Pengetahuan Pemandu Parawisata Di Desa Blitar Sebrang Kabupaten Rejang Lebong Tahun 2022 - Handi Rustandi; Danur Azissah Roesliana Sofais; Ida Samidah; Murwati Murwati; Jipri Suyanto; Darmawansyah Darmawansyah (Jurnal Multidisiplin Dehasen (MUDE), 2023)
Background. The provision of first aid must be done quickly and accurately by using the facilities and infrastructure available at the scene. A first aid action that is done properly will reduce disability or suffering and even save the victim from death, but if the first aid action is not carried out properly it can even worsen the accident and even cause death, a tour guide must be able to provide security and safety to every tourist who visits. Health education is all activities to provide and improve the knowledge, attitudes, practices of individuals, groups or communities in maintaining and improving their own health. Purpose of this study was to determine the effect of Health Education Roleplay on First Aid in Accidents (P3K) on the Knowledge of Tourist Guides in Blitar Sebrang Village, Rejang Lebong Regency. Methods This research is analytical research with Pre Experimental Design (The One Group Pre-Test-Post Test Design). The sampling technique used stratified random sampling. The number of respondents is 35 people. Results of statistical tests before and after the intervention of health education about first aid in accidents (P3K) on the knowledge of tour guides showed a significant effect with the P-Value = 0.000 less than 0.05. Conclusion There is an Influence of Health Education Roleplay on First Aid in Accidents (P3K) on Knowledge of Tourist Guides in Blitar Sebrang Village, Rejang Lebong Regency.